The effect of partially pregelatinized cassava starch as disintegrant for paracetamol tablet - Okta Nama Putra; Winni Nur Auli; Musa Musa; Derina Paramitasari; Gabriela Kasih Mawarni (Pharmaciana, 2022)
The use of partially pregelatinized starch in tablet formulations is entirely various; one of them is disintegrant. Present pregelatinized starch is imported from another country, which is relatively expensive. In contrast, many plants can be used as starch sources, including cassava which is relatively abundant in Indonesia. This study aimed to determine the effect of using partially pregelatinized starch from cassava as a disintegrant in paracetamol tablets. In this study, seven formulas were used with different disintegrants, three formulas using partially pregelatinized starch from cassava with concentrations of F1 5%, F2 10%, and F3 15%, three formulas using Starch 1500 with the same concentration as partially pregelatinized starch from cassava and one control formula without disintegrant. The tablet was made using the wet granulation method. The tablets produced were tested for physical properties (hardness, disintegration, and dissolution). In addition, compact ability of partially pregelatinized starch from cassava was compared with Avicel, Starch 1500, and cassava starch. Based on the results of the study showed that partially pregelatinized starch from cassava produced tablets that tended to be capping with less hardness than tablets with Starch 1500 and control tablets. The compact ability test results showed that the compact ability of partially pregelatinized starch from cassava was better than Starch 1500 and cassava starch. The disintegration test results showed that tablets with partially pregelatinized starch from cassava had faster disintegration than tablets with Starch 1500 and control tablets. The dissolution profile of tablets with partially pregelatinized starch from cassava is also better than other formulas.